Algorithmic Literacy and the Role of Librarians in Its Education - Shahnaz Khademizadeh; Mohammad Amin Sekhavatmanesh (کتابداری و اطلاع‌رسانی)
Objective: Considering the increasing spread of artificial intelligence and its algorithm-oriented nature and the increasing interaction of users with these algorithms in various platforms such as social networks, online stores, and search engines, the present study intends to examine the concept and necessity of algorithmic literacy and, in the following, the role of librarians who are actually specialists in information science in the education and development of this literacy. This research aims to study the concept and necessity of algorithmic literacy and the role of librarians in teaching this literacy. Methodology: This research has been done in a narrative review method. In this way, related articles were extracted by searching the term algorithmic literacy in domestic and foreign reliable scientific databases. Then, this concept was examined and compared in terms of definition, dimensions, components, and other aspects, and consensus, disagreement, and research gaps were revealed. Findings: The review of the literature revealed that despite the fact that researches on algorithmic literacy have been conducted abroad in recent years, this concept has not yet been studied in Iran. In this research, the development of the concept of literacy from the age of information to the age of artificial intelligence was investigated. Different definitions of algorithmic literacy were also mentioned. Next, the dimensions and components of algorithmic literacy and its importance and necessity were discussed. In the end, the role of librarians and libraries in teaching algorithmic literacy was discussed. Conclusion: A look at the definition of literacy from the past to the present shows that the concept of literacy has always been changing due to technological changes. At first, literacy is defined as "the ability to read and write". Then, with the emergence of digital technologies, it is defined as "ability and awareness"; Finally, with technological advances, it is defined as "awareness and critical evaluation skills". All digital technologies are algorithmic machines and depend on algorithms to function. Now that we are in the era of artificial intelligence and artificial intelligence systems are built on the basis of algorithms, the need for literacy in relation to algorithms is felt more and more under the title of "algorithmic literacy". By reviewing the researches, it is clear that there is still no single and universal definition of algorithmic literacy, but by summarizing these researches, we can express this definition: "Awareness and recognition of algorithmic systems along with the ability and skill of critical evaluation of these systems". Also, there is no consensus on the dimensions and components of algorithmic literacy, and researchers have examined different dimensions, which overlapped in some cases. What emerges from the research review is that algorithmic literacy is related to the cognitive, behavioral and emotional dimensions of the user. If in the age of information, human interaction with information was investigated, today, in the era of artificial intelligence and algorithms, human interaction with algorithms should be investigated. Since in the past, libraries played an important role in teaching information literacy and librarians were its pioneers, now librarians and information science specialists can play a role as algorithmic literacy educators, according to their inherent duty.